2005
DOI: 10.2139/ssrn.653583
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion of Environmental Policy Innovations: A Contribution to the Globalisation of Environmental Policy

Abstract: Nutzungsbedingungen: Dieser Text wird unter einer Deposit-Lizenz (Keine Weiterverbreitung-keine Bearbeitung) zur Verfügung gestellt. Gewährt wird ein nicht exklusives, nicht übertragbares, persönliches und beschränktes Recht auf Nutzung dieses Dokuments. Dieses Dokument ist ausschließlich für den persönlichen, nicht-kommerziellen Gebrauch bestimmt. Auf sämtlichen Kopien dieses Dokuments müssen alle Urheberrechtshinweise und sonstigen Hinweise auf gesetzlichen Schutz beibehalten werden. Sie dürfen dieses Dokume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 78 publications
1
44
0
2
Order By: Relevance
“…Other articles, however, linked to the broader literature on common property regimes (CPRs) or "the commons" and were strongly informed by scholars such as Ostrom (1990) and Agrawal (2001), among others (e.g., Corbera et al 2009, Fisher et al 2010, Muñoz Escobar et al 2013. Swallow et al (2010) integrated multiple theoretical perspectives in their analysis including examining the conditions necessary for policy diffusion provided by Kern et al (2001). Despite the strong connections of several articles to the broader theoretical literature, over half the articles we reviewed were not clearly linked to a theoretical perspective and were largely theory neutral.…”
Section: Linking Payments For Ecosystem Services (Pes) Enabling Condimentioning
confidence: 99%
“…Other articles, however, linked to the broader literature on common property regimes (CPRs) or "the commons" and were strongly informed by scholars such as Ostrom (1990) and Agrawal (2001), among others (e.g., Corbera et al 2009, Fisher et al 2010, Muñoz Escobar et al 2013. Swallow et al (2010) integrated multiple theoretical perspectives in their analysis including examining the conditions necessary for policy diffusion provided by Kern et al (2001). Despite the strong connections of several articles to the broader theoretical literature, over half the articles we reviewed were not clearly linked to a theoretical perspective and were largely theory neutral.…”
Section: Linking Payments For Ecosystem Services (Pes) Enabling Condimentioning
confidence: 99%
“…The national government is both the subject and object of global environmental policy learning and lesson-drawing (Rose, 1993;Bennett, 1991;Kern et al, 2001;Tews et al, 2003). Compared with actors at other policy levels national governments are relatively strong players acting under the highest pressure for innovation in relevant problem areas.…”
Section: In the Context Of Multi-level Environmental Governance The mentioning
confidence: 99%
“…This resulted in a list of factors that various authors have posited as important or necessary for successfully scaling up and/or out from a pilot stage (Rogers, 1962(Rogers, , 2010Rogers and Shoemaker, 1971;Granovetter, 1978;Kemp et al, 1998;Kern et al, 2001;Moore, 2002;Gershon, 2009;Rosenberg, 2011;World Health Organization ExpandNet, 2011;Management Systems International, 2012;Ardoin et al, 2013;Butler et al, 2013;Sutton and Rao, 2014, UNDP Small Grants Programme, Stanford ChangeLabs, unpublished). While some of these authors cited real-world examples of scaling success throughout their papers (Kern et al, 2001;Rosenberg, 2011;World Health Organization ExpandNet, 2011;Management Systems International, 2012;Ardoin et al, 2013 UNDP Small Grants Programme), the discussion of which factors were most important to ensure success were largely theoretical. Furthermore, we found no empirical evaluations of the association of these factors with scaling success.…”
Section: Putative Principles For Scaling Successmentioning
confidence: 99%
“…Although many of the factors and principles that authors have suggested will improve the individual-individual transmission of ideas may also be useful when considered in a larger-scale context, there are other factors that appear to be important in the spread of innovations between groups. For example, Kern et al (2001) describe conditions likely to facilitate or hinder the spread of environmentally-relevant policies from one country to another. In their book Scaling Up Excellence, Sutton and Rao (2014) detail an extensive set of principles and tactics they argue can ease and ensure the successful growth of companies and organizations across sectors.…”
Section: Introductionmentioning
confidence: 99%